Effect of conjugated linoleic acid overproducing Lactobacillus with berry pomace phenolic extracts on Campylobacter jejuni pathogenesis. Issue 1 (19th December 2018) - Tabashsum, Zajeba; Peng, Mengfei; Kahan, Eliana; Rahaman, Shaik O.; Biswas, Debabrata
Abstract : Prebiotics or prebiotic-like components such as bioactive phenolics from berry pomace can stimulate the growth of beneficial microbes including Lactobacillus casei and its metabolites, and competitively inhibit the growth of enteric bacterial pathogens like Campylobacter jejuni . Abstract : Campylobacter jejuni (CJ) is one of the predominant causative agents of acute gastroenteritis in the US and other developed countries through the handling of raw chicken or the consumption of undercooked poultry and poultry products. Probiotics and their metabolites such as conjugated linoleic acids (CLAs) play a crucial role in improving host health and act as antimicrobials against enteric pathogens. Furthermore, prebiotics or prebiotic-like components such as bioactive phenolics from berry pomace can stimulate the growth of beneficial microbes including Lactobacillus casei (LC) and its metabolites, and competitively inhibit the growth of enteric bacterial pathogens. In this study, we aimed at enhancing the efficiency of antimicrobial/beneficial activities of LC and the extent of production of bioactive compounds by combining berry pomace phenolic extract (BPPE) and overproducing CLA in L. casei (LC-CLA). Under mixed culture conditions, LC-CLA in the presence of BPPE reduced the growth of CJ by more than 3 log CFU ml −1 within 48 h. The cell-free culture supernatant (CFCS) of LC-CLA in the presence of BPPE also reduced significantly the growth of CJ >3.2 log CFU ml −1 at 24 h. The interactions of CJ with cultured chicken fibroblast cells (DF-1), chicken macrophage (HD-11), and human epithelial cells (HeLa) were altered significantly. Treatments with BPPE and/or CFCS also altered the injured cell number, auto-aggregation capacity and cell surface hydrophobicity of CJ, significantly. Furthermore, combined treatments with BPPE and CFCSs of LC-CLA altered the expression of multiple virulence genes such as ciaB, cdtB, cadF, flaA, and flaB of CJ from 0.45 fold to 6.85 fold. Overall, BPPE enhanced the effect of LC-CLA in the reduction of CJ growth, survival ability, host cell–CJ interactions, and virulence gene expression. This finding indicates that a combination of BPPE and LC-CLA may be able to prevent the colonization of CJ in poultry, reduce the cross-contamination of poultry products and control poultry-borne campylobacteriosis in humans.